Sosialisasi Pentingnya Pendidikan Tinggi di Madrasah ‘Aliyah Raudlatul Ulum Ledokombo Jember - Nasirudin Al Ahsani; Husniatul Haliyah; Mita Apriliya Faradipa; Nailiyah Basirah (Jurnal Al-Tatwir, 2023)
In Ledokombo Village, there are two assets that can be optimized, namely individual and social assets. In terms of individual assets, the author sees that teenagers in Ledokombo Village have good academic potential. Meanwhile, in terms of social assets, there is a Karang Taruan community as a forum for teenagers to channel their aspirations. The socialization of the importance of higher education for graduates of equivalent level Islamic schools aims to provide understanding and motivation to equivalent level Islamic school students who will graduate, so that they can consider and decide to continue their education to higher education levels, considering the importance of higher education in preparing future generations with broad knowledge to be empowered in national development in the future. This service uses the Asset Based Community Development (ABCD) method. The activity was carried out at MA Raudlatul Ulum and attended by 2 classes of 3rd grade students. The activity went smoothly according to the plan, which was socialization and discussion related to the importance of higher education. The result of this activity is that the participants have a better understanding and motivation to continue their education to higher education levels after graduating from Madrasah Aliyah in the future.